Here is how you can set up the two-column proof for showing that \(\angle 6\) and \(\angle 11\) are congruent in the parallelogram:
| Statement | Reason | |-------------------------------------------------------|----------------------------------------| | 1. \(a \parallel b\) and \(e \parallel f\) | Given | | 2. \(m\angle 5 + m\angle 6 = 180^\circ\) and \(m\angle 9 + m\angle 11 = 180^\circ\) | Definition of linear pair | | 3. \(m\angle 5 = m\angle 13\) and \(m\angle 9 = m\angle 13\) | Corresponding Angles Theorem | | 4. \(m\angle 13 + m\angle 6 = 180^\circ\) and \(m\angle 13 + m\angle 11 = 180^\circ\) | Subtraction Property of Equality | | 5. \(m\angle 13 + m\angle 6 = m\angle 13 + m\angle 11\) | Transitive Property of Equality | | 6. \(m\angle 6 = m\angle 11\) | Substitution Property of Equality |
This organizes the steps, statements, and reasons coherently in a way that logically leads to the conclusion that \(\angle 6\) and \(\angle 11\) are congruent.